2011
DOI: 10.1038/mt.2010.243
|View full text |Cite
|
Sign up to set email alerts
|

Application of Phi29 Motor pRNA for Targeted Therapeutic Delivery of siRNA Silencing Metallothionein-IIA and Survivin in Ovarian Cancers

Abstract: Ovarian cancer is a highly metastatic and lethal disease, making it imperative to find treatments that target late-stage malignant tumors. The packaging RNA (pRNA) of bacteriophage phi29 DNA-packaging motor has been reported to function as a highly versatile vehicle to carry small interference RNA (siRNA) for silencing of survivin. In this article, we explore the potential of pRNA as a vehicle to carry siRNA specifically targeted to metallothionein-IIa (MT-IIA) messenger RNA (mRNA), and compare it to survivin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Due to its stability and self-assembling properties in vitro, pRNA has been used successfully as a scaffold in the rational design of functional RNA supramolecular structures (Chen et al 2000;Shu et al 2004Shu et al , 2011bShu et al , 2013Guo 2005;Guo et al 2005Guo et al , 2006Li et al 2009Li et al , 2015aTarapore et al 2011;Haque et al 2012;Khisamutdinov et al 2014). Compared to phi29 pRNA, the stabilities of other natural and mutated pRNA sequences remain relatively underexplored (Shu et al 2011a;Li et al 2015b).…”
Section: Future Improvements In Predicting Rna 3wj Stabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its stability and self-assembling properties in vitro, pRNA has been used successfully as a scaffold in the rational design of functional RNA supramolecular structures (Chen et al 2000;Shu et al 2004Shu et al , 2011bShu et al , 2013Guo 2005;Guo et al 2005Guo et al , 2006Li et al 2009Li et al , 2015aTarapore et al 2011;Haque et al 2012;Khisamutdinov et al 2014). Compared to phi29 pRNA, the stabilities of other natural and mutated pRNA sequences remain relatively underexplored (Shu et al 2011a;Li et al 2015b).…”
Section: Future Improvements In Predicting Rna 3wj Stabilitiesmentioning
confidence: 99%
“…Recent studies have shown that the SF5 and M2 pRNAs have the highest propensities for in vitro self-assembly (Gu and Schroeder 2011;Hao and Kieft 2014). The shape, self-assembly properties, and stability of pRNA can be leveraged in the rational design of functional supramolecular structures, including polyvalent nanoscale delivery systems (Chen et al 2000;Shu et al 2004Shu et al , 2011bShu et al , 2013Guo 2005;Guo et al 2005Guo et al , 2006Li et al 2009Li et al , 2015aTarapore et al 2011;Haque et al 2012;Khisamutdinov et al 2014). However, an important consideration in the design of functional nanostructures is the stability of the pRNA "building block" (Shu et al 2011a;Li et al 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Recent crystal structures of an engineered phi29 pRNA (Ding et al 2011), and of an isolated phi29 pRNA three-way junction (lacking the kissing interactions) (Zhang et al 2013) provided additional details of the intermolecular and intramolecular interactions that are important within this specific pRNA species. The knowledge resulting from these diverse studies of the phi29 pRNA has led to its adaptation as a polyvalent delivery vector and it has been useful for various types of RNA engineering (Guo et al , 2006Li et al 2009;Wendell et al 2009;Shu et al 2011;Tarapore et al 2011;Ye et al 2012;Khisamutdinov et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicate that the pRNA-siRNA chimera exerts the silencing function of siRNA effectively and that the silencing efficiency of this chimera is similar to or even better than that of free siRNA (Zhang et al, 2009;Tarapore et al, 2011). Similarly, the pRNA-aptamer chimera interacts with the specific receptor, as expected (Guo et al, 2005; Figure 6.…”
Section: Discussionmentioning
confidence: 99%